"Off the court". Numeric gender representation in Italian women's basketball - Manuela Picariello; Lars Dzikus (SHARE Press, 2020)
The present study investigates gender dynamics in the Italian top women's basketball league, Serie A1, specifically numeric gender representation in off-the-court leadership positions and its potential influence on production relations and power relations, the first two dimensions of Connell's (2002) model. Italy is historically a country with a dominant patriarchal society and few women in leadership and decision-making positions. We performed frequency counts of gender by team and position and performed frequency distribution looking at 14 teams during the 2019-2020 season. A gender division emerged because men assumed the majority of off-the-court positions in the league. Men prevailed over women in power relations, occupying the most influential positions in the teams. There are very few women in leadership positions in the Italian teams. It is possible that the underrepresentation of women contributes to a lack of gendered emotional relations and the assumptions that male dominance is "natural."